The effect of organizational culture on the performance of UAE organizations - Noora AlShehhi; Fatima AlZaabi; Mohammed Alnahhal; Ahmad Hasan Sakhrieh; Mosab I. Tabash (Cogent Business & Management, 2021)
This study investigates the relationship between organizational culture (OC) and the performance of organizations in the United Arab Emirates (UAE). A theoretical framework to measure this relationship in the UAE is designed. Interviews with experts and questionnaires were conducted to prioritize certain identifiers and indicators of the relationship between organizational culture and performance in the context of the UAE. The OC-performance relationship framework was analyzed and tested. The number of respondents from the UAE organizations is 131. The results of the study showed a positive relationship between organizational culture and performance, and this relationship is especially stronger with job satisfaction. Moreover, the results also indicate that there is no evidence of any difference between the performance of organizations in the public and private sectors. Furthermore, the degree of implementation of the positive OC constructs varies from one construct to another. These positive OC constructs are goal achievement, employee engagement and commitment, and team spirit. This research is one of the few, if not the first, to investigate the relationship between OC and organizational performance in the private and public organizations in the UAE. The study would be useful for managers to concentrate on the cultural dimensions that enhance organizational performance.
Keywords: 650; organizational culture; performance; UAE; financial constructs; business environment